Balancing evidence and frontline experience in the early phases of the COVID-19 pandemic: current position of the Italian Society of Anti-infective Therapy (SITA) and the Italian Society of Pulmonology (SIP). (July 2020) - Bassetti, M.; Giacobbe, D.R.; Aliberti, S.; Barisione, E.; Centanni, S.; De Rosa, F.G.; Di Marco, F.; Gori, A.; Granata, G.; Mikulska, M.; Petrosillo, N.; Richeldi, L.; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of coronavirus disease 2019 (COVID-19), which has rapidly become epidemic in Italy and other European countries. The disease spectrum ranges from asymptomatic/mildly symptomatic presentations to acute respiratory failure. At the present time the absolute number of severe cases requiring ventilator support is reaching or even surpassing the intensive care unit bed capacity in the most affected regions and countries. Objectives: To narratively summarize the available literature on the management of COVID-19 in order to combine current evidence and frontline opinions and to provide balanced answers to pressing clinical questions. Sources: Inductive PubMed search for publications relevant to the topic. Content: The available literature and the authors' frontline-based opinion are summarized in brief narrative answers to selected clinical questions, with a conclusive statement provided for each answer. Implications: Many off-label antiviral and anti-inflammatory drugs are currently being administered to patients with COVID-19. Physicians must be aware that, as they are not supported by high-level evidence, these treatments may often be ethically justifiable only in those worsening patients unlikely to improve only with supportive care, and who cannot be enrolled onto randomized clinical trials. Access to well-designed randomized controlled trials should be expanded as much as possible because it is the most secure way to change for the better our approach to COVID-19 patients.